The Effect of Orange Inhalation Aromatherapy on Anxiety in Chronic Kidney Failure Patients Undergoing Hemodialysis - Hasna Fadhilah Qotrunnada; Arina Maliya (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Chronic renal failure patients undergoing hemodialysis often experience anxiety. The patient's anxiety stems from the patient still not knowing how the hemodialysis procedure works and its side effects. The changes experienced by chronic renal failure patients are anxiety, which causes drastic changes in patients not only physically but also mentally. This study aims to determine the effect of orange inhalation aromatherapy on anxiety in patients with chronic renal failure undergoing hemodialysis. This study is a type of experimental research with a two-group pretest-posttest design conducted at Sebelas Maret University Hospital Surakarta in March 2024. The population in this study were 77 patients with chronic renal failure undergoing hemodialysis. The sampling technique of this study was purposive sampling, so the number of samples in this study was 30, consisting of 15 control groups and 15 treatment groups. Data collection on anxiety of chronic renal failure patients was carried out using the Hamilton Anxiety Rating Scale (HARS). Data analysis test in this study used independent samples t-test. The results showed that there were differences in the effect of anxiety in patients with chronic renal failure in the control group who were not given citrus inhalation aromatherapy and the treatment group given citrus inhalation aromatherapy at Sebelas Maret University Hospital with a p-value = 0.012. It is suggested that patients with chronic renal failure undergoing hemodialysis can apply it themselves when experiencing anxiety during hemodialysis because this inhalation aromatherapy is very easy to apply and very useful Keywords: Aromatherapy, chronic kidney failure, hemodialysis, inhalation